MAP Kinase PrMPK9-1 Contributes to the Self-Incompatibility Response. Issue 2 (6th April 2017) - Chai, Lijun; Tudor, Richard L.; Poulter, Natalie S.; Wilkins, Katie A.; Eaves, Deborah J.; Franklin, F. Christopher H.; Franklin-Tong, Vernonica E.
Abstract : A TDY-class MAPK is functionally involved in mediating self-incompatibility in Papaver. Abstract: Mitogen-activated protein kinases (MAPKs) form important signaling modules for a variety of cellular responses in eukaryotic cells. In plants, MAPKs play key roles in growth and development as well as in immunity/stress responses. Pollen-pistil interactions are critical early events regulating pollination and fertilization and involve many signaling events. Self-incompatibility (SI ) is an important mechanism to prevent self-fertilization and inbreeding in higher plants and also is known to utilize signaling to achieve incompatible pollen rejection. Although several pollen-expressed MAPKs exist, very little is known about their function. We previously identified a pollen-expressed MAPK (p56) from Papaver rhoeas that was rapidly activated during SI ; several studies implicated its role in signaling to SI -induced programmed cell death involving a DEVDase. However, to date, the identity of the MAPK involved has been unknown. Here, we have identified and cloned a pollen-expressed P. rhoeas threonine-aspartate-tyrosine (TDY) MAPK, PrMPK9-1 . Rather few data relating to the function of TDY MAPKs in plants currently exist. We provide evidence that PrMPK9-1 has a cell type-specific function, with a distinct role from AtMPK9 . To our knowledge, this is the first study implicating a function for a TDY MAPK in pollen. We show that PrMPK9-1 corresponds to p56 and demonstrate that it is functionally involved in mediating SI in P. rhoeas pollen: PrMPK9-1 is a key regulator for SI in pollen and acts upstream of programmed cell death involving actin and activation of a DEVDase. Our study provides an important advance in elucidating functional roles for this class of MAPKs.